Patients' Evaluation of a Preparatory Online Communication Tool for Older Patients With Cancer Preceding Chemotherapy. Issue 2 (March 2020) - Driesenaar, Jeanine A.; van Dulmen, Sandra; van Weert, Julia C. M.; Noordman, Janneke
Abstract : Background: The online tool PatientVOICE has been developed to enhance older patients' participation during educational nursing encounters preceding chemotherapy and to increase their information recall. Objective: The aim of this study was to evaluate perceived usefulness, usability, satisfaction with emotional support, language use, attractiveness, and visit intention of PatientVOICE by older (ex-)patients with cancer. Methods: Older (ex-)patients with cancer were invited to evaluate the website via an online questionnaire. Perceived usefulness, usability, and satisfaction with emotional support were measured using evaluation statements, the System Usability Scale, and an adapted subscale of the Website Satisfaction Scale, respectively. Questions were also included about language use and attractiveness of the website and patients' intention to visit the website. Results: A total of 44 questionnaires were analyzed. Many patients evaluated the provided information and other integrated techniques (such as the question prompt sheet, video fragments, and the audio facility) positively on aspects as usefulness and helpfulness. The usability was considered good (mean scale score, 74.3). Most patients (84.9%) considered the language use on the website clear, and 63.6% of the patients found the website attractive. Many patients (71.9%) would visit the website if they would like to gather information on the encounter preceding chemotherapy, and 62.5% of the patients would do this for information about chemotherapy. Conclusions: PatientVOICE is evaluated as a useful and user-friendly tool, enabling patients to prepare themselves for the nursing encounter preceding chemotherapy and to gather information about chemotherapy. Implications for Practice: Preparatory online tools, such as PatientVOICE, can be implemented in hospitals to offer patients extra support.